Transformers rescue bots. [videorecording (DVD)] Heroes of tech. - Burton, LeVar; Chabert, Lacey, 1982-; Blum, Steve, 1965- (Transformers, Rescue Bots., 2016)
Chase, Heatwave, Blades and Boulder, and a family of first responders will do whatever it takes to protect both their home and the world. They learn that new technology can assist them in wondrous ways, but it can also have consequences if misused. Join the Rescue Bots team as experimental technology turns Cody into an adult, a space elevator strands Doc and Graham in orbit, a new invention causes the entire town to sing instead of talk and more.